2021
DOI: 10.31557/apjcp.2021.22.9.3039
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs 0064286 and 0000475: Potential Diagnostic Biomarkers in Hepatocellular Carcinoma

Abstract: Objective: Hepatocellular carcinoma (HCC) is considered the highest recorded malignancy in Egypt. The shortage of appropriate biomarkers for early detection often results in the late diagnosis of the HCC. Circular RNAs (CircRNAs) are presented as long stranded non-coding RNA that combine covalently to make a sealed circular form which make them very stable. CircRNAs are known to have interpretative role in cancer development and metastasis. Aim: To examine the dysregulation of two new CircRNAs obtained from Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Satellite nodule, lymph node metastasis/vascular invasion, and abnormal elevation of total bilirubin are important risk factors for HCC metastasis, liver function impairment, and poor prognosis 36,37 . Many studies have reported that circRNAs are closely related to the malignant phenotype of HCC, showing the characteristics of crucial clinical markers of disease 38–40 . Hepatitis B virus infection is a major risk factor for HCC patients in East Asia, and early screening and diagnosis of this high‐risk population remains particularly important 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite nodule, lymph node metastasis/vascular invasion, and abnormal elevation of total bilirubin are important risk factors for HCC metastasis, liver function impairment, and poor prognosis 36,37 . Many studies have reported that circRNAs are closely related to the malignant phenotype of HCC, showing the characteristics of crucial clinical markers of disease 38–40 . Hepatitis B virus infection is a major risk factor for HCC patients in East Asia, and early screening and diagnosis of this high‐risk population remains particularly important 41 .…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 Many studies have reported that circRNAs are closely related to the malignant phenotype of HCC, showing the characteristics of crucial clinical markers of disease. 38 , 39 , 40 Hepatitis B virus infection is a major risk factor for HCC patients in East Asia, and early screening and diagnosis of this high‐risk population remains particularly important. 41 In this study, we identified that circSLC39A5 was significantly downregulated in HCC tissues and was associated with satellite nodules, lymph node metastasis/vascular invasion, high bilirubin, and high HBsAg, suggesting that circSLC39A5 is closely related to the progression of HCC patients, and circSLC39A5 may be used as a potential biomarker for early screening of HCC in high‐risk population.…”
Section: Discussionmentioning
confidence: 99%
“…肝细胞癌(HCC)是最常见的原发性肝癌(占病 例的 75-85%) ,也是世界上继肺癌、结直肠癌和胃癌 之后的第四大癌症相关死亡原因 [1]。 HCC 是一种高致 死率的肿瘤,大多数病例在晚期才被发现,发病率与 死亡率之比接近 1。例如,2015 年约有 85.4 万例肝癌 新发病例, 而全世界每年约有 81 万例肝癌相关死亡 [2]。 HCC 高危人群管理中的一个主要问题是早期诊断检 测的敏感性 [1]。 研究表明, 早期诊断的患者可早期治疗, 预后良好,5 年生存率>70% [3]。目前,活检的组织学评 估仍然是癌症组织检测的金标准 [4,5],虽然肝活检具有 较高的敏感性和特异性,是最可靠的诊断方法,但由于 其侵袭性和不良反应,在临床中的应用仍受到限制。此 外,未能识别转移和复发高危患者也导致 HCC 患者预后 不理想。因此众多学者一直致力于研究特定生物标志物 作为 HCC 早期诊断和预后工具。环状 RNA(CircRNA) 是一种新型的内源性非编码 RNA,由蛋白质编码 mRNA 或线性非编码 RNA"反向剪接"产生,它们连接上游 3'剪 接位点和下游 5'剪接位点, 形成共价封闭的环状结构 [6][7][8]。 它们高度稳定、丰富、保守,参与多种生理病理过程, 可能是癌症发生的关键因素。目前,Fathial 等人 [9]发现 has_circ_0064286 可作为 HCC 诊断的潜在生物标志物 (AUC=0.97)。此外,上调的 hsa_circ_0001020 与侵袭 性特征显著相关,可能是 HCC 患者总生存期(OS)的 一个危险因素 [10]。此前,一些已发表的荟萃分析报道了 circRNA 对 HCC 的诊断和预后价值 [11][12][13][14]。然而纳入的 研究和患者相对较少,并且缺乏该领域的最新研究数据。 因此,我们进行了这项荟萃分析,以总结 CircRNA 的失 调与 HCC 的诊断和预后之间的关系。…”
Section: 引言unclassified